Determination of Chromium Mineral in Foodstuffs in Indonesia using INAA Method - Nurcahyani Fatmawati; Yusuf Saeful; Istanto; Suprapti Siti; Alfian; Mulyaningsih Th Rina; Hermana Ferly; Amalia Firda; Dewi Sari Hasnah (E3S Web of Conferences, 2024)
The concentration of the element chromium (Cr) was determined in 76 types of food ingredients from four provinces in Indonesia. The element Cr is one of the essential elements needed by the human body for physiological processes. Although the amount needed for Cr is relatively small, this mineral is very important for the insulin hormone to function properly. Chromium deficiency can result in decreased insulin sensitivity, glucose intolerance and an increased risk of diabetes. The Cr element was determined using the Instrumental Neutron Activation Analysis (INAA) method in the GA. Siwabessy Multipurpose Research Reactor. The reactor which is located in the Puspiptek area has a thermal neutron flux of around 5.47 x 1013 n.cm-2s-1 . Bombardment Cr-50 in foodstuffs samples by thermal neutrons will produce Cr-51 through the n, nuclear reaction. The radiosotope Cr-51. The radiosotope Cr-51 which is the result of thermal neutron activation has a half-life of 27.7 days. The single energy peak of the Cr- 51 gamma-ray can be observed at 320.08 keV. The results showed that cassava leaves, melinjo leaves, watercress, sweet potato leaves, papaya leaves, ipomoea aquatica, kenikir, pumpkin leaves, spinach and mushrooms are foodstuffs rich in Cr compared to other foodstuffs. Foodstuffs from Pandeglang Regency-Banten Province have relatively higher Cr concentrations than other three locations.The concentration of Cr in foodstuffs ranges from 0.039 to 5.244 µg/g.